Medical economics: an integrated approach to the economics of health - Obermann, Konrad; Thielscher, Christian (Agenda Publishing, 2022)
Health economics has become an established field of enquiry over recent years and is now an important contributor to normative health policy, and decisions concerning the allocation of resources and the quality of healthcare provision across the world.Medical Economics, written by two physicians who are also qualified economists, introduces readers to the core economic considerations in healthcare provision and management. Addressing concerns that are relevant to both the individual and to public health, the authors draw on a wider range of economic tools and analytical frameworks than typically offered by standard textbooks. Combining thought experiments with real-world examples they illustrate the healthcare challenges facing today's policy-makers.The book is aimed specifically at courses in medicine, public health, and healthcare management and administration, but also at economists looking for a broader perspective on healthcare systems, including healthcare financing, markets, the role of the state and other macroeconomic considerations, evaluation methods, healthcare technology, paying for medical care, health insurance and ethical issues.